2021
DOI: 10.3389/phrs.2021.1603990
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Inflammatory Bowel Disease: A Model of Microbial, Immune and Neuropsychological Integration

Abstract: Objective: Inflammatory bowel diseases (IBDs) are complex chronic inflammatory disorders of the gastro-intestinal (GI) tract with uncertain etiology. IBDs comprise two idiopathic disorders: Crohn’s disease (CD) and ulcerative colitis (UC). The aetiology, severity and progression of such disorders are still poorly understood but thought to be influenced by multiple factors (including genetic, environmental, immunological, physiological, psychological factors and gut microbiome) and their interactions. The overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 312 publications
(328 reference statements)
0
46
0
4
Order By: Relevance
“…(c) The dysregulation of MALT1 was positively correlated with microbial pathogens, which had been reported to be associated with the inflammatory status in IBD patients. 48 , 49 , 50 Therefore, MALT1 was related to inflammation indexes in IBD patients.…”
Section: Discussionmentioning
confidence: 94%
“…(c) The dysregulation of MALT1 was positively correlated with microbial pathogens, which had been reported to be associated with the inflammatory status in IBD patients. 48 , 49 , 50 Therefore, MALT1 was related to inflammation indexes in IBD patients.…”
Section: Discussionmentioning
confidence: 94%
“…IBD, comprising Crohns disease (CD) and ulcerative colitis (UC), is a gut-related disorder that affects the intestinal tract. The most widely reported symptoms of IBD involve diarrhea, intermittent nausea and vomiting, rectal bleeding, and abdominal pain or tenderness ( Tavakoli et al, 2021 ; Baumgart & Sandborn, 2007 ; Strober et al, 2007 ). Most of these symptoms occur due to intestinal damage which happens as a result of the exaggerated inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Zanoli et al [112] reported an association between depression, Crohn's disease, and cardiovascular complications. Common symptoms associated with IBD is diarrhea, rectal bleeding, intermittent nausea and abdominal pain or tenderness [57]. Although the authors [112] did not associate changes in gut microbiota with any of these symptoms, it is likely that an imbalanced microbiome did play a role.…”
Section: Anxiety and Depressionmentioning
confidence: 94%
“…Chemical signals generated by EECs, either directly or in response to microbial metabolites, travel through the ENS and regulates digestion, salivation, lacrimation, urination, defecation and sexual arousal [56]. A clear association exists between chronic stress and gut inflammation disorders, such as IBD and IBS [57]. Signals from the CNS are sent back to EECs and gut microbiota via the ENS and peripheric nervous system (PNS) [58].…”
Section: Gut Microbiota Alters Neural Signalsmentioning
confidence: 99%